EXPERIENCES IN SOLVING URBANIZATION PROBLEMS - Xolmirzayev Nodirjon Nizomjonovich (Bright Mind Publishing, 2025)
The article discusses the processes of urbanization, the problems they cause, and the experience of Latin America, Japan, South Korea, China, and India.
Keywords: Urbanization, agglomeration, “Latin American trap”, megalopolis, poverty, urban crime, Calcutta-Damodar belt